1991
DOI: 10.1128/mcb.11.6.3395
|View full text |Cite
|
Sign up to set email alerts
|

Cloning by differential screening of a Xenopus cDNA that encodes a kinesin-related protein.

Abstract: By differential screening of a Xenopus egg cDNA library, we selected nine clones (Egl to Eg9) corresponding to mRNAs which are deadenylated and released from polysomes soon after fertilization. The sequence of one of these clones (Eg5) revealed that the corresponding protein has the characteristic features of a kinesin-related protein. More specifically, Eg5 was found to be nearly 30% identical to a kinesin-related protein encoded by bimc, a gene involved in nuclear division in Aspergillus nidulans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 26 publications
0
80
0
Order By: Relevance
“…Agreements to the consensus, within the acceptable substitution range, are indicated by upper case letters. Kiplp from S. cerevisiae (Roof et at., 1992); bimC from A. nidulans (Enos and Morris, 1990); cut7 from S. pombe (Hagan and Yanagida, 1990); Eg5 from Xenopus laevis (Le Guellec et al, 1991); kinesin heavy chain from Drosophila melanogaster (Yang et al, 1989). members of the kinesin-related superfamily, the motor domains of bimC, cut7, Cin8p, Kiplp, and Eg5 from Xenopus laevis (Le Guellec et al, 1991) are most closely related in primary sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Agreements to the consensus, within the acceptable substitution range, are indicated by upper case letters. Kiplp from S. cerevisiae (Roof et at., 1992); bimC from A. nidulans (Enos and Morris, 1990); cut7 from S. pombe (Hagan and Yanagida, 1990); Eg5 from Xenopus laevis (Le Guellec et al, 1991); kinesin heavy chain from Drosophila melanogaster (Yang et al, 1989). members of the kinesin-related superfamily, the motor domains of bimC, cut7, Cin8p, Kiplp, and Eg5 from Xenopus laevis (Le Guellec et al, 1991) are most closely related in primary sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the kinesin-5 family are conserved in the amino acid sequence of the motor (forceproducing) domain and apparently perform similar roles in many different cell types (1)(2)(3)(4)(5)(6)(7). Kinesin-5 motors are required for bipolar spindle assembly, and elimination of their function blocks this essential early mitotic step in fungal, insect, and mammalian cells (8 -11).…”
mentioning
confidence: 99%
“…In nonproliferating cells and tissues in adults, the expression of KSP remains undetectable, whereas its expression is prominent in proliferating cells and tissues during development. 20,55 Increased expression of Eg5 reportedly is associated with tumorigenesis. For example, Castillo et al 20 demonstrated that transgenic mice that overexpressed Eg5 were prone to the development of a variety of tumors.…”
Section: Kinesin-5 Familymentioning
confidence: 99%